(untitled) (Texas Journal of Philology, Culture and History, 2022)
The article is devoted to defining the theoretical and methodological foundations of lifestyle research. For this, first of all, it is necessary to carry out a theoretical explanation of the "lifestyle" category, that is, to reveal the relationship between the content and structural elements of the concept. Also, in order to study the specific aspects of human lifestyle from a scientific standpoint, it is necessary to analyze it not only in a static state, but also in a dynamic state. Relying on these two theoretical approaches used in all lifestyle studies, revealing the lifestyle as a concept that expresses a specific form of human individual or collective life activity, determining the structural structure of the lifestyle, expressing the main properties of the elements included in this composition, and revealing the forms of the lifestyle according to the character ; the issue of showing the factors that cause the emergence of positive and negative lifestyles has been studied.